The Spontaneous pneumothorax port of call consultation - Matlawene J. Mpe (South African Family Practice)
Smokers have an approximately 12% lifetime risk of developing a primary spontaneous pneumothorax. It is rarely life-threatening and is mainly treated by aspiration. Secondary spontaneous pneumothoraces occur mostly in patients with chronic obstructive pulmonary disease, they have a mortality rate of approximately 1% and most patients require a tube thoracostomy with instillation of a sclerosing agent. Successful prevention of recurring secondary pneumothoraces requires more invasive surgical procedures. This article provides a short overview of spontaneous pneumothorax and its treatment.